Inflationary Kaluza- Klien Cosmic String In Scalar-Tensor Theory Of Gravitation - Satish Janjeti (International Journal of Advances in Applied Sciences, 2014)
Abstract We have investigated a spatially homogeneous and anisotropic Kaluz-Klien space time with cosmic strings in the presence of Sen Dunn theory as source. Exact solutions of the Einstein field equations are presented via a suitable power law assumption. Some of models obey geometric strings, massive strings and Takabayasi’s equation of state .We find that the constant value of deceleration parameter is reasonable for the present day universe. Some physical and geometric behaviour of the models are also discussed.